Can pioglitazone be potentially useful therapeutically in treating patients with COVID-19? (2020)
The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has become a pandemic disease (COVID-19) that has spread globally causing more than 30,000 deaths. Despite the immense and ongoing global effort, no efficacious drugs to fight this plague have been identified and patients admitted to the intensive care units (ICU), for respiratory distress, are managed mostly by means of supportive care based on oxygen maintenance. Several authors have reported that the prevalence of hypertension, diabetes, cardiovascular and cerebrovascular diseases comorbidities were indeed frequent among patients with COVID-19, which suggests that these conditions are likely to aggravate and complicate the prognosis. What the aforementioned diseases have in common is a latent chronic inflammatory state that may be associated with the alteration of laboratory parameters that are typical of the metabolic syndrome and insulin resistance. In severe COVID-19 patients laboratory markers of inflammation such as C-reactive protein, IL-6, D-dimer, serum ferritin and lactate dehydrogenase are elevated in many patients; assessed since the 4th-6th day of illness onset, such increases seem to be predictive of an adverse prognosis. Our hypothesis is that drugs belonging to the family of thiazolidinediones (TZD) such as pioglitazone or rosiglitazone, approved for treating the condition of insulin resistance and the accompanying inflammation, could ameliorate the prognosis of those COVID-19 patients with diabetes, hypertension and cardiovascular disorders comorbidities. TZD are PPARγ agonists that act on nuclear receptors, thereby triggering certain transcription factors. TZD were widely used for type-2 diabetes in the first decade of this century and although concerns have been raised for possible side effects associated with long-term treatment, their use has been recently revaluated for their anti-inflammatory properties in numerous medical conditions